Conjugated Microporous Polymers with Bipolar and Double Redox‐Active Centers for High‐Performance Dual‐Ion, Organic Symmetric Battery. Issue 20 (14th April 2021) - Wang, Heng‐guo; Li, Qiang; Wu, Qiong; Si, Zhenjun; Lv, Xiaoling; Liang, Xitong; Wang, Huilin; Sun, Lin; Shi, Weidong; Song, Shuyan
Abstract: Redox‐active conjugated microporous polymers (RCMPs) have received remarkable interest in electrochemical energy‐storage systems in view of their porous structure and tunable redox nature. This work presents an effective strategy to construct RCMPs with bipolar and double redox‐active centers by integrating copper (II) tetraaminephthalocyanine (CuTAPc) and 1, 4, 5, 8‐naphthalenetetracarboxylic dianhydride (NTCDA) units into the RCMPs (CuPcNA‐CMP). As expected, CuPcNA‐CMP has potential application in the half cells of dual‐ion batteries (lithium based DIBs, LDIBs), asymmetric DIBs (graphite based DIBs, ADIBs), and symmetric DIBs (all organic DIBs, SDIBs). Among them, LDIBs show a high reversible capacity (202.4 mAh g −1 at 0.2 A g −1 ) and excellent rate capability (86.1 mAh g −1 at 5 A g −1 ). And ADIBs also show a high reversible capacity (245.3 mAh g −1 at 0.1 A g −1 ), long cycle stability with capacity retention of 89% after 500 cycles, and good rate performance (125.1 mAh g −1 at 5 A g −1 ). In addition, SDIBs show high initial charge/discharge capacities of 269.4/198.5 mAh g −1 at 0.05 A g −1 and a high cell voltage of 2.5 V. Meanwhile, the mechanism of CuPcNA‐CMP on hosting both anions (PF6 − ) and cations (Li + ) is investigated by detailed experimental analysis and density functional theory studies. Abstract : A novel strategy is presented to design and synthesize a redox‐active conjugated microporous polymer (RCMP) with bipolar and double redox‐active centers by integrating metal phthalocyanine and aromatic dianhydride. This RCMP can serve as a universal electrode material for lithium based dual‐ion batteries (DIBs), graphite‐based DIBs, and all organic symmetric DIBs and the reaction mechanism is unveiled by detailed experimental analysis and density functional theory studies.